Salvia-Nelumbinis naturalis improves lipid metabolism of NAFLD by regulating the SIRT1/AMPK signaling pathway - Yang Liu; Yiping Li; Jue Wang; Lili Yang; Xiao Yu; Ping Huang; Haiyan Song; Peiyong Zheng (BMC, 2022)
Abstract Background Salvia-Nelumbinis naturalis (SNN), the extract of Chinese herbal medicine, has shown effects on NAFLD. This study aims to explore the underlying mechanism of SNN for regulating the lipid metabolism disorder in NAFLD based on the SIRT1/AMPK signaling pathway. Methods Male C57BL/6J mice fed with a high-fat diet (HFD) were used to establish the NAFLD model. Dynamic changes of mice including body weight, liver weight, serological biochemical indexes, liver histopathological changes, and protein level of AMPK and SIRT1 were monitored. After18 weeks, SNN treatment was administrated to the NAFLD mice for another 4 weeks. Besides the aforementioned indices, TC and TG of liver tissues were also measured. Western blot and quantitative RT-PCR were used to detect the expression and/or activation of SIRT1 and AMPK, as well as the molecules associated with lipid synthesis and β-oxidation. Furthermore, AML12 cells with lipid accumulation induced by fatty acids were treated with LZG and EX527 (SIRT1 inhibitor) or Compound C (AMPK inhibitor ) to confirm the potential pharmacological mechanism. Results Dynamic observation found the mice induced by HFD with gradually increased body and liver weight, elevated serum cholesterol, hepatic lipid accumulation, and liver injury. After 16 weeks, these indicators have shown obvious changes. Additionally, the hepatic level of SIRT1 and AMPK activation was identified gradually decreased with NAFLD progress. The mice with SNN administration had lower body weight, liver weight, and serum level of LDL-c and ALT than those of the NAFLD model. Hepatosteatosis and hepatic TG content in the liver tissues of the SNN group were significantly reduced. When compared with control mice, the NAFLD mice had significantly decreased hepatic expression of SIRT1, p-AMPK, p-ACC, ACOX1, and increased total Acetylated-lysine, SUV39H2, and SREBP-1c. The administration of SNN reversed the expression of these molecules. In vitro experiments showed the effect of SNN in ameliorating hepatosteatosis and regulating the expression of lipid metabolism-related genes in AML12 cells, which were diminished by EX527 or Compound C co-incubation. Conclusions Taken together, the SIRT1/AMPK signaling pathway, involved in hepatic lipid synthesis and degradation, plays a pivotal role in the pathogenesis of NAFLD development. The regulation of SIRT1/AMPK signaling greatly contributes to the underlying therapeutic mechanism of SNN for NAFLD.